1970
DOI: 10.2105/ajph.60.3.459
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study on the relationship between mental illness and traffic accidents--a pilot study.

Abstract: Dischargees from the State Mental Hospital were evaluated for traffic accidents and violation rates both before and after hospitalization and rates were matched to appropriate comparison groups that were not hospitalized. Rates were higher as a group than the matched comparison groups; however, some subgroups improved after discharge. Single-car accidents occurred almost solely in the hospitalized group. Other findings point to the need for more sophisticated programs to control death and (isability on the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Most of the excess accidental deaths are from falls and aspiration [22]. Some older studies in the US [23] and Denmark [24] did not find an increased rate for road traffic accidents while others found an approximately two-fold incidence of traffic accidents per mile driven by schizophrenic outpatients compared to healthy controls [25,26] (for review see [27]). Similar results were reported in a more recent study by Edlund et al [28] indicating that the absolute mortality from road traffic accidents is reduced in schizophrenia but, since fewer people with schizophrenia drive, the risk per mile driven is probably increased.…”
Section: Risk Of Accidents In Schizophreniamentioning
confidence: 99%
“…Most of the excess accidental deaths are from falls and aspiration [22]. Some older studies in the US [23] and Denmark [24] did not find an increased rate for road traffic accidents while others found an approximately two-fold incidence of traffic accidents per mile driven by schizophrenic outpatients compared to healthy controls [25,26] (for review see [27]). Similar results were reported in a more recent study by Edlund et al [28] indicating that the absolute mortality from road traffic accidents is reduced in schizophrenia but, since fewer people with schizophrenia drive, the risk per mile driven is probably increased.…”
Section: Risk Of Accidents In Schizophreniamentioning
confidence: 99%
“… • Each of the mental illness groups showed a statistically higher violation rates than the control group, particularly in reckless driving, negligent driving and driving with defective equipment. CEBM: level 4 AAN: Class III Eelkema (1970) [ 48 ]; USA; N To examine the correlation between mental illness and crashes N = 238, driving records from a hospital (1960); with matched comparison group ( n = 290) Quantitative: Epidemiological analysis of secondary data Measures: • Crashes • Violations pre and post hospitalisation • Patients discharged from the hospital showed higher crash and violation rates per year. • Greater crash ratio (>1) was found in people with psychosis and psychoneurosis; however, these groups had better records compared to the matched comparison group post discharge (crash ratio < 1).…”
Section: Resultsmentioning
confidence: 99%
“…From this study it appears that those with personality disorders are having crashes due to the behavioural manifestations of their condition; that is, they undertake risky behaviours that impact on their ability to drive safely. Elkema, Brosseau, Koshnick, and McGee [ 48 ] also reported the highest crash rate of those with mental health conditions was those with personality disorders. In this study, it was noted that the behavioural traits demonstrated by those with personality disorders were very different in substance to those with significant mental illness due to depression and bi-polar disorders, associated with an impairment of executive level function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also true that people with psychiatric disorders may have a higher risk of RTAs. Most dangerous appear to be those with dementia followed, in turn, by hypomania and mania, severe depression with suicidal ideation, personality disorders, and neurotic disorders, including anxiety states 8–10 . The ability to estimate speed is likely to be impaired in people experiencing a hypomanic episode due to increased psychomotor activity and may increase the risk of RTAs.…”
Section: The Literaturementioning
confidence: 99%